Evaluating festival attributes adopting S-D logic: The mediating role of visitor experience and visitor satisfaction. (March 2019) - Troisi, Orlando; Santovito, Savino; Carrubbo, Luca; Sarno, Debora
To symbolize the importance of contextual factors of provision in the contemporary service era, in festival research, the term festivalscape has been proposed. Despite the large number of works investigating the construct, extant research does not adequately assess the systemic and interactive nature of festivals, which can be viewed as a set of interconnected elements. To bridge this gap, this article evaluates four festival attributes (atmosphere, service quality, people interaction and collateral services) according to service-dominant logic and service-ecosystem view. Current work examines a light festival organized in Salerno during the Christmas holiday using a sequential regression analysis, revealing the mediating role of experience and satisfaction in influencing behavioural intention.